1995
DOI: 10.1111/j.1348-0421.1995.tb02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Survey ofBartonella (Rochalimaea) henselaein Domestic Cats in Japan

Abstract: A total of 199 domestic cat serum samples from 3 geographical areas (northeastern, central and southwestern) of Japan collected between 1992 to 1994 were examined for serum antibody against Bartonella henselae using an immunofluorescent assay. The antibody prevalence was 15.1% (30/199). A significant difference in the prevalence of B. henselae antibody was observed between the northeastern area (6.3%:3/48) and the central area (22.0%: 13/59) in Japan. There was no significant difference between the average age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 14 publications
1
33
1
7
Order By: Relevance
“…The positive rate in male cats was significantly higher than that of female ones. Other studies also showed that seropositivity of male cats was higher than that of female ones [4,27]. These data may suggest that male cats have more chances to be infected with the agent by fights during the estrus period.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The positive rate in male cats was significantly higher than that of female ones. Other studies also showed that seropositivity of male cats was higher than that of female ones [4,27]. These data may suggest that male cats have more chances to be infected with the agent by fights during the estrus period.…”
Section: Discussionmentioning
confidence: 48%
“…In Japan, the average seropositive rate to B. henselae in cats was reported to be 15.1% [27]. This study revealed that 9.1% of pet cats were seropositive for B. henselae.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…An indirect fluorescence antibody (IFA) test for the detection of antibodies to B. henselae has been increasingly used for the diagnosis and epidemiologic studies of CSD (7,8,11). Serological study of B. henselae in domestic cats revealed the prevalence of cats infected with B. henselae in Japan (9). There are no reports of a serological response to B. henselae in patients with CSD in Japan.…”
mentioning
confidence: 99%